Estudo sobre as mudanças nos sistemas de medição de desempenho causadas pela implantação de práticas de sustentabilidade - Leite, Luciana Rosa (Universidade Federal de São Carlos, 2014)
The research in performance measurement (PM) systems have reacted to changes in organizations environments. In recent years, in response to the pressures of society, the organizations are increasingly implementing sustainability practices. Following this context, this study aims to investigate empirically the changes in PM systems caused by the implementation of sustainability practices in organizations. The bibliometric studies and systematic literature review have showed that there is no clear relationship between the research on sustainability and PM systems. Hence, it is necessary to develop more empirical studies to close the identified gap. In the first research effort of this thesis, a case study was carried out in a company which is ranked as sustainability company in Brazil index. The empirical findings indicate that the PM system changes have occurred in three elements: performance measures, how the companies communicate their results, and the process of information management. These findings were the foundation for developing the survey, the second research effort. The survey was carried out in a population of 182 companies which publish sustainability reports in Brazil, according to the Global Reporting Initiative standards . After the data collection, 81 valid responses were received. The data analyzes demonstrate that the respondents who perceived change in PM systems work in companies which has more implemented environmental practices. Additionally, this perception is influenced by PM systems variables: use of social indicators, the relevance of social/environmental indicators, the new social/environmental performance indicators, the internal communication among all hierarchical classes of roles, the external communication to several groups of stakeholders, the use of benchmarking, the compliance with regulations issues, the information provided from PM system about social/environmental performance measures and the interpretation of the social/environmental performance indicator results. Therefore, the sustainability practices have acted as triggers for changes in performance measurement systems.
Study on performance measurement systems changes caused by the implementation of sustainability practices
Keywords: Sistemas de medição de desempenho; Sustentabilidade; Evolução dos sistemas de medição de desempenho; Performance measurement system; Sustainability; Performance measurement system evolution; ENGENHARIAS::ENGENHARIA DE PRODUCAO